1996
DOI: 10.2176/nmc.36.880
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem Schwannoma —Case Report—

Abstract: A 68-year-old female presented with rare brainstem schwannoma manifesting as right hemiparesis, diplopia, and dysphagia. Neuroimaging revealed a lesion in the pons and cerebral peduncle, which was supposed to be a highly malignant glioma. The mass was approached via a single-flap orbitozygomatic craniotomy through an anteromedial pericavernous approach. Intraoperative frozen-section specimens indicated glioma, but the tumor was distinct from the surrounding parenchyma, and could be removed successfully. A tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…4 Our review of literature revealed only 6 cases of intraparenchymal schwannomas located in the brain stem. 1,[5][6][7][8][9] Our case has unique and interesting features compared with other cases in the literature: 1) Our patient, at 68 years of age, tied with 1 other patient as the oldest on record (and this other elderly patient had an incidentally discovered lesion in the setting of ischemia 9 ).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…4 Our review of literature revealed only 6 cases of intraparenchymal schwannomas located in the brain stem. 1,[5][6][7][8][9] Our case has unique and interesting features compared with other cases in the literature: 1) Our patient, at 68 years of age, tied with 1 other patient as the oldest on record (and this other elderly patient had an incidentally discovered lesion in the setting of ischemia 9 ).…”
Section: Discussionmentioning
confidence: 68%
“…4 Our review of literature revealed only 6 cases of intraparenchymal schwannomas located in the brain stem. 1,[5][6][7][8][9] Our case has unique and interesting features compared with other cases in the literature: 1) Our patient, at 68 years of age, tied with 1 other patient as the oldest on record (and this other elderly patient had an incidentally discovered lesion in the setting of ischemia 9 ).2) The high level of symptoms in our patient developed during 2 weeks; in the other 6 cases, symptoms developed from 6 weeks to 3 years. 3) Perhaps related to this acute presentation, our case is the second one 10 with recorded T2 signal-intensity abnormality surrounding the lesion (of 3 cases with MR imaging available 1,6,9 ).…”
mentioning
confidence: 54%
“…However, these findings were not specific to intraparenchymal schwannoma and always resulted in tentative preoperative diagnoses of low grade glioma. 3,4,12,18,19,23,25,28,31) Although the tumor in our case fulfilled two of the characteristic features, the possibility of an intraparenchymal schwannoma was not considered because we were not aware of this rare entity preoperatively.…”
Section: Discussionmentioning
confidence: 81%
“…11) However, thorough immunohistochemical investigations were performed in only 41 cases, based on our literature review. 1,[3][4][5][6][7][8][9]12,13,[16][17][18][19][20][21][22][23][24][25][26][28][29][30][31] Only these cases were considered in the following discussion. Unlike vestibular schwannomas, intraparenchymal schwannomas tend to occur in young patients, with slight male predominance ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation